Templating gold nanorods with liquid crystalline DNA. (9th January 2015) - De Sio, Luciano; Annesi, Ferdinanda; Placido, Tiziana; Comparelli, Roberto; Bruno, Vincenzo; Pane, Alfredo; Palermo, Giovanna; Lucia Curri, Maria; Umeton, Cesare; Bartolino, Roberto
A bstract: A liquid crystalline, negatively charged, whole-genome DNA is exploited to organize positively charged gold nanorods (GNRs) by means of electrostatic interaction. A mesoscopic alignment of the composite system along a preferred direction is obtained by casting a droplet of the DNA-nanorods solution onto an untreated glass substrate. Gel electrophoresis analysis enables evaluating the effective electric charge of the system, thus minimizing the DNA fragmentation. Polarized optical microscopy, combined with transmission and scanning electron microscopy, shows that, up to 20% in weight of GNR solution, the system exhibits both a long range order, induced by the liquid crystalline phase of the DNA, and a nanoscale organization, due to the DNA self-assembly. These evidences are confirmed by a polarized spectral analysis, which also points out that the optical properties of GNRs strongly depend on the polarization of the impinging probe light. The capability to organize plasmonic nanoparticles by means of DNA material represents a significant advance towards the realization of life science inspired optical materials.